Correlation between the triglyceride-glucose index and chronic kidney disease among adults with metabolic-associated fatty liver disease: fourteen-year follow-up - Wei, Suosu; Wu, Tengyan; You, Yanwu; Liu, Fei; Hou, Qiyan; Mo, Chongde; Zhou, Lei; Yang, Jianrong (Frontiers in Endocrinology, 2024)
Background and aims: According to previous studies, triglyceride-glucose (TyG) is related to chronic kidney disease (CKD), but no studies have explored the correlation between TyG and CKD among adults with metabolic dysfunction-associated fatty liver disease (MAFLD). We aimed to explore the associations of the TyG index with CKD among adults with MAFLD. Methods: In this retrospective observational cohort study, data from 11,860 participants who underwent a minimum of three health assessments between 2008 and 2015 were retrospectively collected. Participants were followed up until the final medical visit or health examination. CKD refers to an eGFR < 60 mL/min per 1•73 m 2 or the occurrence of two or more incidents of proteinuria. Results: Within a median 10•02-year follow-up period, 2005 (16•9%) participants reported developing CKD. Multivariate Cox regression models indicated a noticeable correlation between the TyG index and CKD incidence (HR per unit increase, 1.19; 95% CI: 1.09-1.29) and between the TyG index and CKD incidence (HR per SD increase, 1.12; 95% CI: 1.06-1.18). The CKD incidence increased by 1.8 times in participants in the highest TyG index quartile relative to patients in the lowest quartile of the TyG index quartile (HR 1•18, 95% CI: 1.01-1.38, P = 0.007). According to subgroup analysis, an elevated TyG index is likely to become more harmful to participants younger than 60 years (P for interaction = 0.035). Conclusions: An elevated TyG index may increase CKD incidence among MAFLD adults, particularly among younger people. Early intervention may help reduce the incidence of CKD.